H2O2 Exfoliation of TiO2 for Enhanced Hydrogen Production from Photocatalytic Reforming of Methanol - Syaahidah Abdul Razak; Hasliza Bahruji; Abdul Hanif Mahadi; Hong Wan Yun (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2022)
Hydrogen is considered a future energy carrier for clean and sustainable technology. Photocatalytic reforming of methanol produced hydrogen using water and energy from sunlight. This study reported enhanced activity of TiO2 without metal co-catalyst for hydrogen production following H2O2 exfoliation. TiO2 was transformed into peroxo-titania species on the outer layer of the particles, resulting in surface exfoliation. The exfoliation reduced TiO2 crystallite sizes enhanced the surface hydroxyl group and reduced the band gap to 3.0 eV. Hydrogen production from methanol-water mixtures on the TiO2 after four consecutive exfoliations was measured at 300 µmol, significantly higher than the fresh TiO2 (50 µmol). H2O2 exfoliated TiO2 reduced the pathway for charge migration to the surface. A high concentration of surface hydroxyl group trapped the charge carriers for efficient hydrogen production. Copyright © 2022 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).